Epithelial electrolyte transport physiology and the gasotransmitter hydrogen sulfide - Pouokam, Ervice; Althaus, Mike; Justus Liebig University Giessen (My University, 2016)
Hydrogen sulfide (H2S) is a well-known environmental chemical threat with an unpleasant smell of rotten eggs. Aside from the established toxic effects of high-dose H2S, research over the past decade revealed that cells endogenously produce small amounts of H2S with physiological functions. H2S has therefore been classified as a gasotransmitter. A major challenge for cells and tissues is the maintenance of low physiological concentrations of H2S in order to prevent potential toxicity. Epithelia of the respiratory and gastrointestinal tract are especially faced with this problem, since these barriers are predominantly exposed to exogenous H2S from environmental sources or sulfur-metabolising microbiota. In this paper, we review the cellular mechanisms by which epithelial cells maintain physiological, endogenous H2S concentrations. Furthermore, we suggest a concept by which epithelia use their electrolyte and liquid transport machinery as defence mechanisms in order to eliminate exogenous sources for potentially harmful H2S concentrations.
Keywords: ddc:630